Revisiting current National Comprehensive Cancer Network (NCCN) high-risk prostate cancer stratification: a National Cancer Database analysis - Garg, Harshit; Dursun, Furkan; Alsayegh, Fadi; Wang, Hanzhang; Wu, Shenghui; Liss, Michael A.; Kaushik, Dharam; Svatek, Robert S.; Mansour, Ahmed M. (Prostate cancer and prostatic diseases, 2024)
Background High-risk prostate cancer includes heterogenous populations with variable outcomes. This study aimed to compare the prognostic ability of individual high-risk factors, as defined by National Comprehensive Cancer Network (NCCN) risk stratification, in prostate cancer patients undergoing radical prostatectomy. Methods We queried the National Cancer Database from 2004 to 2018 for patients with non-metastatic high-risk prostate cancer who underwent radical prostatectomy and stratified them as Group H1: Prostate specific antigen (PSA) > 20 ng/ml alone, Group H2: cT3a stage alone and Group H3: Gleason Grade (GG) group 4/5 as per NCCN guidelines. The histopathological characteristics and rate of adjuvant therapy were compared between different groups. Inverse probability weighting (IPW)-adjusted Kaplan–Meier curves were utilized to compare overall survival (OS) in group H1 and H2 with H3. Results Overall, 61,491 high-risk prostate cancer patients were identified, and they were classified into Group H1 ( n = 14,139), Group H2 ( n = 2855) and Group H3 ( n = 44,497). Compared to group H1 or H2, pathological GG group > 3 ( p < 0.001), pathological stage pT3b or higher ( p < 0.001), lymph nodal positive disease (pN1) ( p < 0.001) and rate of adjuvant therapy ( p < 0.001) were significantly in Group H3. IPW-adjusted Kaplan–Meier curves showed significantly better 5-year OS in group H1 compared to group H3 [95.1% vs 93.3%, p < 0.001] and group H2 compared to group H3 [94.4% vs 92.9%, p < 0.001]. Conclusion PSA > 20 ng/ml or cT3a stage in isolation have better oncologic and survival outcomes compared to GG > 3 disease and sub-stratification of ‘High-risk’ category might lead to better patient prognostication.